Trust Giving Transactions on Mu'amalah Al-Wadi'ah - Saiful Bahri; Syarkawi Syarkawi; Mursal Mursal; Fizazuawil Fizazuawil; Maimun Maimun (Budapest International Research and Critics University, 2019)
The practice of mu'amalah al-Wadi'ah in Indonesian is often termed by liter literary savings, which is currently underway among the people through Bakn Syari'ah institution. Definition of wadi'ah, even though there is a diversity of editors in the formulation of the meaning, but substantially does not show fundamental differences, it's just that there are editorial differences between including and representing. So it can be understood that wadi'ah is giving power to someone who is trusted to maintain certain assets in a certain way. The legal basis for Wadiah is found in Qur'an, Surat al-Nisa verse: 58, and Surat al-Baqarah, verse: 283. Besides that, there is also a legal basis in the hadith, a History of the abi of David, and the ijmak of the scholars.